2018
DOI: 10.1111/bjet.12649
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood educators’ attitudes and beliefs around the use of touchscreen technologies by children under three years of age

Abstract: This paper reports on an Australian study around early childhood educators’ attitudes and beliefs on the use of touchscreen technologies by very young children, under three years of age. The study adopted an ecological perspective and educators and directors of early childhood centres completed an online survey and were interviewed on this specific topic. Data were analysed to identify teachers’ competencies (eg, digital skills) but also possible factors behind attitudes and beliefs (eg, leadership styles; tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 24 publications
0
25
0
3
Order By: Relevance
“…Za uporabo izobraževalne tehnologije pri zgodnjem učenju so med ključnimi dejavniki digitalna pismenost in spretnosti vzgojiteljev (Hatzigianni in Kalaitzidis, 2018). Razvoj digitalnih spretnosti in uporaba digitalne tehnologije sta odvisna od pojmovanja in stališča učiteljev o uporabnosti izobraževalne tehnologije (Istenič Starčič in .…”
Section: Dejavniki Uporabe Izobraževalne Tehnologijeunclassified
“…Za uporabo izobraževalne tehnologije pri zgodnjem učenju so med ključnimi dejavniki digitalna pismenost in spretnosti vzgojiteljev (Hatzigianni in Kalaitzidis, 2018). Razvoj digitalnih spretnosti in uporaba digitalne tehnologije sta odvisna od pojmovanja in stališča učiteljev o uporabnosti izobraževalne tehnologije (Istenič Starčič in .…”
Section: Dejavniki Uporabe Izobraževalne Tehnologijeunclassified
“…Educators' philosophy is also worth further exploration as recommended by previous studies (Hatzigianni and Kalaitzidis 2018;Lynch and Redpath 2014;Lindahl and Folkesson 2012;House 2012). Overall, in this study constructivist approaches (statements 2 and 4), appeared to be the most eminent views.…”
Section: Discussionmentioning
confidence: 99%
“…confidence) to such usage (Blackwell, Lauricella, and Wartella 2014;Ertmer et al 2012). More recently Hatzigianni and Kalaitzidis (2018) focusing on children under 3 years of age in Australia offered a new insight into the factors impacting integration of technology into Early Childhood Education by underlining the role of the teachers' pedagogical philosophy.…”
Section: Literature Review and Social Contextsmentioning
confidence: 99%
“…Furthermore, there is little evidence of digital technologies being embedded in the curriculum in ways that support the development of new and creative practices around technology. Although practitioners may be open to change, they remain unconvinced about the use of technology in play (Hatzigianni and Kalaizidis 2018) and do not use their pedagogical skills to support child-initiated learning with technology (Morgan 2010;Vangsnes and Økland 2015). Although research into the use of digital technologies in early childhood education is in its infancy, it has identified that there are many unresolved issues in the effective integration of technology into child-centred learning environments (Kewalramani and Havu-Nuutinen 2019).…”
Section: Introductionmentioning
confidence: 99%